Exploring social media usage among different generations of Thai farmers - Phusamphao, Nantaphon; Suvittawat, Adisak (Edelweiss Applied Science and Technology, 2024)
Social media’s pervasive influence extends to the agricultural sector, driving transformative changes. The purpose of this study aims to comprehensively overview how different generations of Thai farmers utilize social media. It has two principal objectives: first, to explore farmers’ behavior in relation to the frequency of social media use, their preferred platforms, and engaging advertising formats; and second, to examine the correlation between different generations of farmers and their choice of social media platforms. The study employed purposive sampling and quantitative methodologies to survey Thai farmers, utilizing questionnaires for data collection and analyzing the data with descriptive statistics. A total of 150 participants took part, evenly distributed across rice cultivation, gardening, and arable crop cultivation. The findings of this study showed that social media platform usage among farmers was found to vary by generation, with each cohort demonstrating distinct preferences for different platforms. It was observed that older generations, such as Baby Boomers and Gen X, tended to concentrate their social media usage on a select few platforms, while younger generations, including Gen Y and Gen Z, exhibited more diversified usage patterns. Therefore, understanding generational differences in social media platform usage among farmers remains crucial for developing targeted communication strategies, facilitating knowledge dissemination, and enhancing market engagement within the agricultural sector. Encouraging the utilization of social media in agricultural promotion initiatives maximizes benefits for farmers and aids in adapting to the changing landscape of the agricultural industry in Thailand in the digital era.